RISK FACTOR OF ROTATOR CUFF TENDINOPATHY: A SYSTEMATIC REVIEW - Fitryati, Firosyi (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Rotator cuff tendinopathy is an umbrella term that  includes  different  shoulder  conditions  affecting  subacromial structures, such as rotator cuff tendinitis/tendinosis, subacromial bursitis and shoulder impingement  syndrome.  Rotator  cuff  tendinopathy  is  refractory to treatments, results in impaired activities of daily living and has a significant socio-economic burden due to loss of work and treatment costs. The aim: This study aims to show risk factor for rotator cuff tendinopathy. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 75 articles, whereas the results of our search on SagePub brought up 151 articles. The results of the search conducted for the last year of 2013 yielded a total 58 articles for PubMed and 53 articles for SagePub. The result from title screening, a total 7 articles for PubMed and 18 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: The most well-established RCD risk factor is advanced age, with higher prevalence associated with age in multiple studies. Other important and potentially modifiable risk factors exist, such as occupational physical demands, but few epidemiologic studies have evaluated associations specific to RCD.